Defining and conceptualizing news literacy. (August 2022) - Tully, Melissa; Maksl, Adam; Ashley, Seth; Vraga, Emily K; Craft, Stephanie
Interest in news literacy inside and outside the academy has grown alongside related concerns about the quality of news and information available. Attempts to fully define, explicate and operationalize news literacy, however, are scattered. Drawing on literature across journalism and mass communication, we propose a definition of news literacy that combines knowledge of news production, distribution and consumption with skills that help audiences assert control over their relationship with news. We propose that knowledge and skills should be conceptualized across five domains: context, creation, content, circulation and consumption. This explication offers a clear, concise and cohesive path for research about news literacy, especially empirical testing to evaluate news literacy and its effectiveness in contributing to relevant behaviours. This framework also offers a consistent, yet flexible, approach to measuring news literacy across diverse contexts.